Cryoablation in Chronic Pain Management: A Narrative Review - Sreyashi Naskar; Debesh Bhoi; Wasimul Hoda; Heena Garg (Indian Journal of Pain)
Cryoneurolysis is a technique of applying extreme cold temperatures to specific sensory nerves, causing a prolonged period of loss of conduction through that nerve. This technique has found widespread application in the field of interventional pain medicine in a variety of conditions including chronic postsurgical pain, phantom limb pain (PLP), and cancer pain. Its use in chronic pain states has been aided further by the advent of handheld cryoneurolysis devices and the widespread use of ultrasonographic imaging to guide and target nerves accurately. Chronic pain states – chronic knee pain from osteoarthritis, refractory PLP, temporomandibular disorders, cervicogenic headaches, low back pain, different peripheral neuropathies, and metastatic bone tumor pain – are some of the conditions where cryoneurolysis has been proven to benefit patients in cases where the symptoms were refractory to other conventionally used modalities. Chronic pain is a complex and multifaceted condition and hence requires a variety of individualized treatment approaches. Current research on this treatment method for chronic pain indicates that it carries low risk and, when used correctly, offers extended pain relief without causing motor function loss. This narrative review includes all types of scientific studies, published between 2010 and 2023, which were selected using a specific set of keywords through two different literature search engines. In conclusion, it explains how cryoneurolysis works to provide long-term pain relief and summarizes the latest evidence supporting its use in chronic pain management.